2008
DOI: 10.1590/s1807-59322008000100007
|View full text |Cite
|
Sign up to set email alerts
|

Trend of Maximal Inspiratory Pressure in Mechanically Ventilated Patients: Predictors

Abstract: Caruso P, Carnieli DS, Kagohara KH, Anciães A, Segarra JS, Deheinzelin D. Trend of maximal inspiratory pressure in mechanically ventilated patients: predictors. Clinics. 2008;63(1):33-8. INTRODUCTION:It is known that mechanical ventilation and many of its features may affect the evolution of inspiratory muscle strength during ventilation. However, this evolution has not been described, nor have its predictors been studied. In addition, a probable parallel between inspiratory and limb muscle strength evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…The real-time identification of alterations in respiratory mechanics is of great interest in both physiopathology studies and in the diagnosis of breathing diseases 1,2. This analysis allows a detailed evaluation of the different phases of the breathing cycle, and it can be made using the interruption technique.…”
Section: Introductionmentioning
confidence: 99%
“…The real-time identification of alterations in respiratory mechanics is of great interest in both physiopathology studies and in the diagnosis of breathing diseases 1,2. This analysis allows a detailed evaluation of the different phases of the breathing cycle, and it can be made using the interruption technique.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have demonstrated that early mobilization is an important component in the care of critically ill patients who require prolonged MV; it facilitates improved lung and muscle function, accelerates the recovery process, and decreases T MV and T ICU ,. (1,7,22,(26)(27)(28)(29)(30) The present study has several limitations. First, there was a difference between the initial values of PImax between the CPTG and the EMG.…”
Section: Discussionmentioning
confidence: 85%
“…The fault in the DVM has as one of the main causes the respiratory muscle weakness [10][11][12] , commonly evaluated by the maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP) 13 ; however, there are only a few studies focusing on the function of expiratory muscles at weaning, whose focus in generally on the inspiratory ones, in particular on the diaphragm [14][15][16] . Thus, reviews and guidelines do not mention the MEP and the expiratory muscle training 10,12,17 .…”
Section: Introductionmentioning
confidence: 99%